Dermatoglyphic Patterns of Finger Tips in the Patients with Pulmonary Tuberculosis (Bangladesh Journal of Anatomy, 2015)
Context: The word dermatoglyphics denotes as the scientific study of the epidermal ridge patterns of fingertips, palm and sole. There are three major classes of dermatoglyphic patterns of finger tips: loops, whorls and arches. Analysis of finger dermatoglyphic is beginning to prove itself as a useful tool for preliminary investigation in conditions with a suspected genetic basis. The genetic contribution is one of the causes of pulmonary tuberculosis. The present study on finger dermatoglyphics pattern was carried out to provide dermatoglyphic as a tool for early prediction of pulmonary tuberculosis by comparing dermatoglyphic patterns of pulmonary tuberculosis patients with the normal healthy individuals.Materials and Methods: A Cross-sectional, analytical type of study was conducted in Department of Anatomy, Dhaka Medical College, Dhaka, from January 2012 to December 2012. The study was performed on 100 patients suffering from pulmonary tuberculosis and 100 healthy individuals.Results: The percentage of whorl in pulmonary tuberculosis patients was significantly higher than control group (P